The Processing of Coffee-based Drinks in Tanah Garam Garam Village, Lubuak Sikarah, Solok - Yuke Permata Lisna; Sulis Purwanto; Alfi Husni Fansurya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Through tourism, the community can take advantage of business opportunities by maximizing the potential of their village. The potential of the developed village starts from agriculture, plantations, and others. The Payo tourist village destination has the potential for coffee, so it can make people manage coffee-based drinks. The purpose of this service is to train the community to be able to manage coffee-based drinks which can then be offered to tourists. The method used is experiment and demonstration. The results of the service show that coffee can be managed into various kinds of drinks with espresso as a base, which are then given training to the community. Training activities started from participant recruitment and discussion, training on Payo coffee-based beverage processing and training on non-coffee drinks. In this training, experiments were carried out by determining the composition of the right coffee drink, so that it could be used as a reference for the community. Thus, the people who are members of the management will become coffee drink entrepreneurs (barista)